Evaluación de dos variedades de lechuga (Lactuca sativa L.), sometida a la aplicación de tres dosis de sulfato de calcio, Cantón Espejo – provincia del Carchi - Cangás Mejía, Silvana de los Ángeles (2018)
VII. SUMMARY The purpose of this research was to study the application of three doses of calcium in the yield of two varieties of lettuce, located in the western sector of the city of El Ángel, called La Calera. It is located at 3000 m.n.m., with the aim of determining what type of application and variety is the most appropriate in the crop yield per hectare and its economic utility. We investigated eight treatments with the combination of three applications of calcium in two varieties of lettuce with a control, using an experimental design Design of Complete Blocks at Random (DBCA) with a factorial arrangement A x B, 8 treatments and 3 repetitions, giving us a total of 24 experimental units. The total area of the experiment was 286.00 m2, with experimental plots of 6.00 m2. The efficiency of the applications of calcium in the yield was evaluated, as it mentions of two varieties of lettuce evaluated with percentage of catch, height of plant, equatorial diameter, weight of cabbage, yield and economic analysis of the treatments, the verification of means of The treatments were performed using Tukey's multiple range test at 5% probability. The results obtained showed that lettuce varieties with calcium applications, generated the highest percentage of yield, silver height, equatorial diameter, cabbage weight, yield which obtained the best net benefit, compared to the control without application. In conclusion, the research cleared doubts in the performance of the lettuce crop with the application of calcium improving the quality and net benefit.